2018
DOI: 10.29328/journal.ibm.1001011
|View full text |Cite
|
Sign up to set email alerts
|

Growth Promoting Potential and Colonization Ability of Probiotics (Bacillus coagulans and Bacillus subtilis) on the Freshwater Prawn Macrobrachium rosenbergii Post-Larvae

Abstract: The probiotic effects of Bacillus coagulans and Bacillus subtilis were studied on survival, growth, concentrations of basic biochemical constituents, activities of digestive enzymes, and their colony establishments in the gut of Macrobrachium rosenbergii post-larvae (PL). Eleven groups of PL (2.03±0.05 in length and 0.18±0.01g in weight), each consists of 35 individuals maintained in 25 L of ground water and fed ad libitum with fi ve serially diluted concentrations, 10 , 10 -7 and 10 -9 of B. coagulans, and B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Studies have revealed that most of the proteins encoded by the B. velezensis genome are involved in carbohydrate and amino acid transport and metabolism [33], thereby decomposing macromolecular nutrients into small molecular polypeptides, amino acids, and fatty acids, among others, which are conducive to absorption, and improving the utilization rate of nutrients in sh feed. Additionally, probiotics can enhance growth performance by producing various digestive enzymes [34]. The B. pumilus strain used in this study was preliminarily selected for its high production of protease, which can effectively decompose and utilize nutritional proteins in animal and plant protein sources.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that most of the proteins encoded by the B. velezensis genome are involved in carbohydrate and amino acid transport and metabolism [33], thereby decomposing macromolecular nutrients into small molecular polypeptides, amino acids, and fatty acids, among others, which are conducive to absorption, and improving the utilization rate of nutrients in sh feed. Additionally, probiotics can enhance growth performance by producing various digestive enzymes [34]. The B. pumilus strain used in this study was preliminarily selected for its high production of protease, which can effectively decompose and utilize nutritional proteins in animal and plant protein sources.…”
Section: Discussionmentioning
confidence: 99%
“…Similar elevations in activities of protease, amylase and lipase have been reported by Jain et al, [39,40] in M. rosenbergii PL fed with E. gallinarum and E. hirae enriched Artemia nauplii. Elevated activities of protease, amylase and lipase have also been recorded in M. rosenbergii PL fed with LactoBasil ® plus, ViBact*, L. sporogenes, Bacillus subtilis, S. cerevisiae, Lactobacillus brevis, Lactobacillus fermentum, B. coagulans and B. licheniformis supplemented feeds [21,22,[24][25][26][27][28][29][30]. It has been reported that a significant increase in activities of digestive enzymes in Penaeus vannamei larvae when using B. coagulans and B. subtilis in its feeding regime [62][63][64].…”
Section: Activities Of Digestive Enzymesmentioning
confidence: 99%
“…They have competitively exclude pathogenic bacteria by production of inhibitory compounds in an ecofriendly manner, increase immune response, stress resistance, disease tolerance, maintain water quality, encourage reproduction and offer better growth and survival [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Probiotics increase digestibility of nutrients and feed efficiency by producing some exogenous enzymes, which increases activities of endogenous enzymes (amylase, protease and lipase) to hydrolyze nutrients, and effectively improve growth, survival and nutritional quality of the host [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In aquaculture, Bacillus coagulans, a spore-forming gram-positive bacterium, has frequently been applied as a feed additive due to its combination of lactic acid bacteria and Bacillus properties [19,20]. Moreover, B. coagulans is known to endure high temperatures, acidity, and bile salts and inhibit enteropathogens [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%